2020
DOI: 10.1101/2020.04.14.040832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic control ofCampylobactercolonisation in broiler chickens: genomic and transcriptomic characterisation

Abstract: 29Campylobacter is the leading cause of bacterial foodborne gastroenteritis in many countries. Source 30 attribution studies unequivocally identify the handling or consumption of contaminated poultry meat as the 31 primary risk factor. One potential strategy to control Campylobacter is to select poultry with increased 32 resistance to colonisation. We conducted genomic and transcriptomic analyses of commercial pedigree 33 broilers exposed to Campylobacter to examine persistent colonisation of the caecum as a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Although we recognise that microbial diversity will increase naturally from day 7 to day 30, based on our data, Campylobacter is associated with an increasing diversity. Broiler genetics is known to impact microbial diversity [47,48] and this may explain why in our study the environmental pressure was significantly impacted positively by the presence of Campylobacter. Here, the environmental influence may be the chicken host genetics influencing microbial community structure.…”
Section: Discussionmentioning
confidence: 74%
“…Although we recognise that microbial diversity will increase naturally from day 7 to day 30, based on our data, Campylobacter is associated with an increasing diversity. Broiler genetics is known to impact microbial diversity [47,48] and this may explain why in our study the environmental pressure was significantly impacted positively by the presence of Campylobacter. Here, the environmental influence may be the chicken host genetics influencing microbial community structure.…”
Section: Discussionmentioning
confidence: 74%
“…Campylobacter is associated with an increasing diversity. Broiler genetics is known to impact microbial diversity [47,48] and this may explain why in our study the environmental pressure was significantly impacted positively by the presence of Campylobacter. Here the environmental influence may be the chicken host genetics influencing microbial community structure.…”
Section: Discussionmentioning
confidence: 74%
“…Differences exist in the levels of colonisation across and within commercial broiler lines [13,14] and these have been associated with variation in the transcriptome of the caeca [14][15][16] and spleen [17]. Genome-wide association studies in a commercial broiler population have indicated that resistance to caecal C. jejuni colonisation is under moderate genetic control [14]. However, heritable differences in resistance have been associated with quantitative trait loci (QTL) [14,18], and the transcription of genes related to immunity [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…One option to achieve this is to improve the intrinsic resistance of chickens to Campylobacter colonisation. Differences exist in the levels of colonisation across and within commercial broiler lines [13,14] and these have been associated with variation in the transcriptome of the caeca [14][15][16] and spleen [17]. Genome-wide association studies in a commercial broiler population have indicated that resistance to caecal C. jejuni colonisation is under moderate genetic control [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation